مدخل مرحلي لتقييم المخططات التنظيمية نحو منهجية تشاركية تحقق المرونة في خطط العمل دراسة حالة مخطط مدينة الزبداني - صيداوي وليد (Latakia University Journal -Engineering Sciences Series, 2019)
أدّت عملية المراوحة التي عانت منها المخططات التنظيمية المدروسة في سوريا في ظل غياب عمليات التقييم ذات المنهجية الواضحة وبقاء الدور التشاركي مجرد ظل يساير عملية الدراسة ويجانب واقع التنفيذ، دوراً سلبياً في عملية التنمية والتطور العمراني، واضعاً أمام المخططين مشكلة كثيراً ما تكررت في المخططات التنظيمية لكثير من المدن السورية مستدعية التدخل الإجرائي الوضعي الذي زاد من سلبيات الوضع المكاني وانعكاسه على العمران. لذلك اتجه البحث لإيجاد آلية تقييم للواقع التنظيمي للمدن السورية واستشراف فرص لآفاق التطوير وطرحها في ظل الواقع المصدق للمخططات التنظيمية والإمكانات المتاحة بهدف التوصل إلى خطة عمل تضمن الوصول للمنتج الهدف ويمكن اعتمادها للتقييم في إطار سيناريوهات وبدائل . The making time process of studied master plans in Syria under the absence of evaluation processes and the existence of participating role as a shadow of study process in addition to avoid the reality of implementation plays a negative role in the process of developing and urban development. Putting before planners a problem which is frequently reoccur in the master plan of most Syrian cities asking the spatial implementing intervention which increases the effect of spatial reality and its reflection on urban itself. So, the research tends to find an evaluation mechanism of organizational reality of Syrian cities, looking up to and putting forth an opportunities of developing horizons in the shadow of authorized reality of master plan and affordable possibilities with the aim to reach an action plan which ensures reaching the targeted product where it can be used to evaluate in the frame of scenarios and alternatives.